PERSEPSI PEGAWAI TERHADAP PELAKSANAAN PENGAWASAN MELEKAT OLEH ATASAN LANGSUNG DI KANTOR UNIT PELAYANAN TEKNIS DINAS PELAYANAN PENDAPATAN PROVINSI DI PADANG - VANIA FEBRI UTAMI (Universitas Negeri Padang, 2018)
This study aimed to describe the perceptions of employees on the implementions of the inherent supervisions by immediate supervisor in the office Unit Pelayanan Teknis Dinas Pelayanan Pendapatan Provinsi Sumatera Barat. A total population of 46 people. The research instrument used in the form of a questionnaire using a Likert scale. The data processed by using the formula of the average (mean). Based on research result obtained revealed that the implementation of the inherent supervision by immediate supervisor in the office Unit Pelayanan Teknis Dinas Pelayanan Pendapatan Provinsi Sumatera Barat already performing well enough with an average score of 3,4 on category quite well